2018
DOI: 10.1007/s11934-018-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

Perianesthetic Management of Laparoscopic Kidney Surgery

Abstract: A variety of laparoscopic approaches (transperitoneal, retroperitoneal, hand-assisted, robotic) are used with some having advantages over others. The kidneys are particularly sensitive to hemodynamic changes and pneumoperitoneum. Controversies in perioperative fluid administration exist. New modalities for postoperative pain control have been suggested. Laparoscopic kidney surgery is associated with multiple physiologic changes and adverse events but offers advantages of reduced postoperative pain, faster reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 87 publications
0
16
0
2
Order By: Relevance
“…Various interventions to prevent acute pain after laparoscopic donor nephrectomy have been described, but their effect on chronic pain has yet to be clarified fully. Perioperative administration of an α 2 agonist (such as clonidine), lidocaine infusion, pregabalin or ketamine have all been described as effective methods for reducing acute postoperative pain and the need for opioid medication. Effective intraoperative interventions are subfascial administration of bupivacaine, transversus abdominis plane block, low‐pressure pneumoperitoneum and deep neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions to prevent acute pain after laparoscopic donor nephrectomy have been described, but their effect on chronic pain has yet to be clarified fully. Perioperative administration of an α 2 agonist (such as clonidine), lidocaine infusion, pregabalin or ketamine have all been described as effective methods for reducing acute postoperative pain and the need for opioid medication. Effective intraoperative interventions are subfascial administration of bupivacaine, transversus abdominis plane block, low‐pressure pneumoperitoneum and deep neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Others found no increased risk of cancer recurrence after TRT post-radiation therapy for prostate cancer [14-15]. A review of the literature on the use of TRT post-treatment for prostate cancer demonstrated generally no significant increases in PSA or recurrence rate [16]. However, there is a lack of randomized controlled studies or studies with large sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of these operation modes (e.g. “pop-dusting”) also represent additional clinical options [ 5 ]. These major modes are briefly summarized in Table 3…”
Section: Holmium:yag Laser Lithotripsy (λ = 2120 Nm)mentioning
confidence: 99%